Memahami makna sumpah dalam Al-Qu’ran - Vidhania, Aiska Rahma (Maliki Interdisciplinary Journal, 2024)
The Quran is the Word of Allah, serving as a guide for human life, and was revealed as a miracle to Prophet Muhammad (peace be upon him) in a language understood by his people. One of the rights of the Quran that must be fulfilled is to ponder its verses, allowing readers to gain wisdom and lessons bestowed by Allah. One of the linguistic styles used by Allah in conveying His sacred message in the Quran is through the use of "Qasam" or oaths. The purpose of these oaths in the Quran is to eliminate any doubt within us regarding the truth conveyed by the magnificent Quran. The word "Qasam" is mentioned 40 times in the Quran, in verses that contain oaths. The name of Allah is used for oaths that express earnestness and warning, while for other oaths, Allah uses the names of His great and chosen creations. Therefore, the oaths in the Qur'an are meant to remove doubt and misunderstanding, as well as to strengthen arguments and confirm news. This is in accordance with the nature of the Arab society, which was accustomed to making oaths. Historically, revelation has been closely intertwined with the traditions of Arab society. The same applies to the function of oaths, which cannot be separated from the social context of the Arab community at that time. Oaths were an integral part of traditions passed down through generations, used as a means to strengthen arguments, reinforce commands, or dispel doubts from opposing parties.